2015
DOI: 10.1242/jcs.161505
|View full text |Cite
|
Sign up to set email alerts
|

The juxtamembrane region of synaptotagmin 1 interacts with dynamin 1 and regulates vesicle fission during compensatory endocytosis in endocrine cells

Abstract: Synaptotagmin 1 (Syt1) is a synaptic vesicle protein that is important for the kinetics of both exocytosis and endocytosis, and is thus a candidate molecule to link these two processes. Although the tandem Ca 2+ -binding C2 domains of Syt1 have important roles in exocytosis and endocytosis, the function of the conserved juxtamembrane ( jxm) linker region has yet to be determined. We now demonstrate that the jxm region of Syt1 interacts directly with the pleckstrin homology (PH) domain of the endocytic protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…The structural differences between unphosphorylated and phosphorylated core region residues in Syt 1 also provide potential insight into a recent report of the IDR interacting with the PH domain of dynamin 1, a GTPase known for facilitating fission of vesicles that are being endocytosed (6). That study showed that a T112E missense mutation in the IDR abolishes the binding interaction, suggesting that phosphorylation is a regulatory mechanism for the interaction.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The structural differences between unphosphorylated and phosphorylated core region residues in Syt 1 also provide potential insight into a recent report of the IDR interacting with the PH domain of dynamin 1, a GTPase known for facilitating fission of vesicles that are being endocytosed (6). That study showed that a T112E missense mutation in the IDR abolishes the binding interaction, suggesting that phosphorylation is a regulatory mechanism for the interaction.…”
Section: Discussionmentioning
confidence: 67%
“…Because the Syt 1 IDR exerts allosteric influence over C2A, structural or disordered ensemble transitions that occur there may be important for modulating C2 domain functions that in turn influence exocytosis (5). Additionally, the IDR was recently shown to bind to the PH domain of dynamin 1, implicating its sequence in an important protein-protein interaction of endocytosis (6).…”
Section: Introductionmentioning
confidence: 99%
“…; McAdam et al . ). Synaptotagmin can also bind with the accessory proteins of endocytosis, such as AP2 and Stone 2 (Fergestad and Broadie ).…”
Section: Discussionmentioning
confidence: 97%
“…As such, it will be important to determine the conditions during which phosphorylation of SV2A's N-terminal domain (T84) occurs, and if this process occurs at the PM. Importantly, Syt1 has been shown to control endocytic events (Li et al, 2017;Nicholson-Tomishima and Ryan, 2004;Poskanzer et al, 2003) and recruit endocytic machinery during endocytosis in endocrine cells (McAdam et al, 2015). The C2 domains of Syt1 regulate the kinetics of vesicle internalisation in a calcium-dependent manner, similar the action of the C2 domains during exocytosis (Yao et al, 2012).…”
Section: Sv2a-mediated Nanoclustering Promotes Syt1 Trafficking To Rab5-positive Early Endosomesmentioning
confidence: 99%